PERBANDINGAN EFEKTIVITAS MEDIA AUDIOVISUAL DAN LEAFLET TERHADAP KEPATUHAN PEMBATASAN CAIRAN PASIEN GGK - Satiti Kusumawardani (Jurnal Ilmiah Kesehatan Media Husada, 2021)
ABSTRACT One of the treatments to save the life of patients with chronic renal failure is hemodialysis therapy, accompanied by fluid intake restriction. This research aimed to figure out the effect of health education using audiovisual media on fluid restriction of Chronic Kidney Failure patients in the Hemodialysis Room of RSUD Dr. Saiful Anwar Malang. This research was a quantitative approach with a quasi-experimental design with a pretest-posttest approach with control group design. The sampling technique used in this research is purposive sampling. In the control group, the score of adherence to fluid restriction in CKD patients was significantly different (p=0.000). In the treatment group, the score of adherence to fluid restriction in CKD patients was significantly different (p=0.000). There was a difference in adherence scores after education between the control group and the experimental group (p=0.040). Education using audio-visual is very effective for increasing one's knowledge. So it is recommended that the next researchers to conduct health education research using the audio-visual method more than one meeting. Keyword: Health Education, Chronic Kidney Disease (CKD), Fluid Intake ABSTRAK Salah satu penanganan untuk menyelamatkan nyawa pasien Gagal Ginjal Kronik adalah terapi hemodialisis, disertai pembatasan asupan cairan. Tujuan dari penelitian ini untuk mengetahui pengaruh pendidikan kesehatan media audivisual terhadap pembatasan cairan pasien Gagal Ginjal Kronik di Ruang Hemodialisa RSUD Dr. Saiful Anwar Malang.Penelitian ini menggunakan pendekatan kuantitatif desain Quasi Eksperiment Teknik sampling yang digunakan purposive sampling. Pada kelompok kontrol, skor kepatuhan pembatasan cairan pada pasien GGK berbeda signifikan (p=0.000). Pada kelompok perlakuan, skor kepatuhan pembatasan cairan pada pasien GGK berbeda signifikan (p=0.000). Terdapat perbedaan skor kepatuhan sesudah edukasi antara kelompok kontrol dan kelompok eksperimen (p=0.040). Edukasi menggunakan audio visual sangat efektif untuk meningkatkan pengetahuan seseorang, sehingga disarankan kepada peneliti selanjutnya untuk melakukan penelitian pendidikan kesehatan menggunakan metode audio visual lebih dari satu kali pertemuan. Kata Kunci: Pendidikan kesehatan, Gagal Ginjal Kronik, Asupan Cairan